(untitled) (Journal of Kidney Cancer, 2024)
The immunosuppression administered to renal transplant recipients to safeguard renal function elevates their susceptibility to renal cancer, which is estimated to be 15 times higher than in the general population. The current study aimed to analyze various aspects of native kidney renal cell carcinoma (RCC) in renal transplant recipients. This study involved a retrospective analysis of 11 patients who underwent nephrectomy for RCC in native kidneys among renal transplant recipients at our institution since 1992. Our institutional incidence was 0.4%. Median age at presentation was 57 (49–60) years. The ratio of male: female was 10:1. Most patients were asymptomatic at presentation and native kidney disease before transplantation was undetermined. In our study, the median time interval between diagnosis of RCC and transplant was 9.1 (8.4–11.2) years. All patients underwent native kidney nephrectomy. Clear cell type was more common than papillary type, 3.5 (2.5–4.2). Ten patients were diagnosed with stage I disease and one patient had stage IV disease. Fuhrman nuclear grading revealed low grades in nine patients and three patients had Grade 3. Immunosuppressive therapy modification was done in nine patients. Meticulous follow-up of renal transplant patients is essential for earlier diagnosis and appropriate treatment of native kidney RCC in transplant recipients. Authors recommend every year follow-up in transplant recipients with special emphasis on ultrasound of native kidney.